The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.5694/mja14.01375
|View full text |Cite
|
Sign up to set email alerts
|

Geographical mobility of general practitioners in rural Australia

Abstract: Objective: To describe the geographical mobility of general practitioners in Australia, both within rural areas and between rural and metropolitan areas. Design and participants: Annual panel survey of GPs between 2008 and 2012. Main outcome measures: Work location, categorised by a typology based on geographical location and community size; frequency of mobility (change of location category); and characteristics of those who moved. Results: There were 3906 participants in 2008 (representative cohort, 19% of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…12 Similarly, we found that the majority of both newly recruited registrars (58% in 2009-2013) and non-registrars (51%) left the rural workforce within 3 years. 12 Similarly, we found that the majority of both newly recruited registrars (58% in 2009-2013) and non-registrars (51%) left the rural workforce within 3 years.…”
Section: Discussionsupporting
confidence: 59%
“…12 Similarly, we found that the majority of both newly recruited registrars (58% in 2009-2013) and non-registrars (51%) left the rural workforce within 3 years. 12 Similarly, we found that the majority of both newly recruited registrars (58% in 2009-2013) and non-registrars (51%) left the rural workforce within 3 years.…”
Section: Discussionsupporting
confidence: 59%
“…25 The eight studies used a range of different analytical methods. 6,23,26 Multiple factors, including some from each of the six broad domains of retention, were consistently found to be significantly associated with rural retention. 27,29 More sophisticated analytical approaches used regression models (including linear, logistic and Cox Proportional Hazards models) which adjusted for multiple factors at once.…”
Section: Resultsmentioning
confidence: 97%
“…Study sample sizes ranged from the relatively small study of 70 former Tasmanian GP Registrars 28 to 4223 Australian rural GPs. 6,[23][24][25][26]28 The highest quality studies were large and able to account for how long PHC workers had already been working in a rural location when assessing the risk of leaving. Several studies tested differences in proportions or differences in means without taking any potential confounders into account.…”
Section: Resultsmentioning
confidence: 99%
“…Increasingly too, graduates are choosing medical specialities over generalist roles, further compounding the difficulties in recruiting and retaining rural primary care doctors 4,5 . Nonetheless, professional satisfaction is often high amongst existing rural primary care doctors 6 , with many rural communities serviced by long-standing doctors 7,8 .…”
Section: Introductionmentioning
confidence: 99%